Analyzing Teachers' Implementation of Authentic Assessment in English Lesson at SMKN 4 Bulukumba - Purnamasari, Ita; Asriati, St; Daddi, Herlina (FKIP Unismuh Makassar, 2023)
This research has to find out (1).How is the teachers’ implementation authentic assessment in English Lesson? (2).What are the problems faced by English teachers in implementation authentic assessment in English lesson?. This research applied descriptive qualitative method. Data collection techniques that used are observation and interview. The result of this research are English teacher in SMKN 4 Bulukumba have implemented authentic assessment. Authentic assessment types that have been applied include oral interview, project/exhibition, and portfolio. The implementing of authentic assessment types shows that the teacher is creative in conducting the assessment.In implementing authentic assessment, English teacher in SMKN 4 Bulukumba have problem such as: (1) limited time, (2) difficult applying authentic assessment to certain competence, and (3) time management.